Pemanfaatan Fungi Mikoriza Arbuskula dan Pot Organik untuk Meningkatkan Pertumbuhan Suren (Toona sinensis Roem.) di Persemaian Permanen IPB Dramaga - Sri Wilarso Budi; Dwi Puspasari Arum Ramadhani (Jurnal Silvikultur Tropika, 2020)
The cultivation of seedling which uses polybag caused the increase of polybag demand. Due to the rising demand of polybag, the rate of pollution caused by polybag waste is increasing as well, so that it requires an alternative to solve the problem by using organic based pot which is environmentally friendly and easily degraded. This study aimed to analyze the effect of Arbuscular Mycorrhizal Fungi (AMF) adding and the utilization of organic based pot to the growth of Suren (T. sinensis) seedling. This study was conducted using completely randomized design with two factor method, as well as observation for 16 weeks. The results showed that the interaction of organic pot composition treatment and AMF addition were significantly affected to the both parameters of height and diameter, while the treatment of organic pot composition was significantly affected to the parameter of total dry weight, moreover the treatment of AMF addition was significantly affected to the parameter of colonization of AMF. The results of this study indicated that the treatment of newspaper: rice husk gave better response of growth than other treatments. Keywords: Arbuscular Mycorrhizal Fungi, suren (T. sinensis), organic pot